Assessing Russia's Decline Trends and Implications for the United States and the U.S. Air Force - Oliker, Olga (RAND Corporation, 2002)
What challenges does today's Russia pose for the United States and the U.S. Air Force? If certain economic, military, social, and political negative trends in Russia continue, they may create a new set of dangers that might prove more real, and therefore more frightening, than the far-off specter of Russian attack ever was. In a number of scenarios, the U.S. Air Force is certain to be called upon for transportation and perhaps for various military missions in a very demanding environment.